1991
DOI: 10.1021/bi00104a011
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and kinetic characteristics of the interaction of the antitumor antibiotic sparsomycin with prokaryotic and eukaryotic ribosomes

Abstract: Using 125I-labeled phenol-alanine sparsomycin, an analogue of sparsomycin having higher biological activity than the unmodified antibiotic, we studied the requirements and the characteristics of its interaction with the ribosome. The drug does not bind to either isolated ribosomal subunits or reconstituted whole ribosomes. For sparsomycin binding to 70S and 80S ribosomes, the occupation of the peptidyltransferase P-site by an N-blocked aminoacyl-tRNA is a definitive requirement. The sparsomycin analogue binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
3
25
0
2
Order By: Relevance
“…To demonstrate unambiguously that sparsomycin was crosslinked to the A2602 region of 23S rRNA, the phenol-alanine derivative of sparsomycin was radioactively labeled, by iodination at the phenol group, to produce [ 125 I]phenol-alanine-sparsomycin (Fig. 1), which retains biological activity (6,19). Proc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate unambiguously that sparsomycin was crosslinked to the A2602 region of 23S rRNA, the phenol-alanine derivative of sparsomycin was radioactively labeled, by iodination at the phenol group, to produce [ 125 I]phenol-alanine-sparsomycin (Fig. 1), which retains biological activity (6,19). Proc.…”
Section: Resultsmentioning
confidence: 99%
“…It is also special in that it binds very weakly, if at all, to ribosomes lacking an N-blocked aminoacyltRNA (6). This effect is reciprocated in that sparsomycin stimulates PЈ-site binding of N-blocked tRNA fragments containing the 3Ј-terminal-CCA-end (4, 7).…”
Section: Sparsomycin (mentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activity resulted from its ability to inhibit the peptide bond-forming step of protein biosynthesis by interacting with the large ribosomal subunit. [7][8][9][10] These potentially important biological activities have made 3 an attractive target for a potential antineoplastic compound. 11) Since thê rst synthetic study of sparsomycin in 1976, 12) synthetic studies of sparsomycin, [13][14][15] total synthesis, [16][17][18] biosynthesis, 19,20) and structure-activity relationship studies [21][22][23][24][25][26][27] have been widely reported.…”
mentioning
confidence: 99%
“…A retrosynthetic analysis was carried out based on Helquist's protocol 18) as summarized in Scheme 1. The structure of sparsomycin might enable it to be produced from 6-methyluracylacryllic acid (8) and the hydroxy-protected amino dithioacetal mono-S-oxide part (III) and to couple these two building blocks by amide formation. The alkyl sulfenyl group of III was prepared by sulfenylation of the methyl sulfoxide (II) with alkyl disulˆde.…”
mentioning
confidence: 99%